PERCEPTIONS OF PROSPECTIVE TEACHERS ON POSTERS WITH SOCIAL THEMES - (:unkn) unknown (REZEKNE HIGHER EDUC INST-REZEKNES AUGSTSKOLA, 2015)
We can't know that can we change the world through the poster which is a product of graphic design but it is possible to make goodness for humankind by designing router and awareness posters since they can redirect and emphasize the ideas with mass media. The aim of this study, which is prepared with this opinion, is determine to prospective teachers' values of perceptions from different classes and different departments. Teachers are so important to have ability to reach and teach all individuals in community. For this reason, in this study 80 prospective teachers will attendduring 2014-2015 school year in Education Faculties of Ondokuz Mayis University and Marmara University. Four different social themed posters selected which contains different values like respect, peace, sensitivity and tolerance, to state how their opinion about social issues. These posters will show to participants and ask about their opinion. The results will evaluate with content analysis.
Keywords: social themed posters; prospective teachers; value perception